2018
DOI: 10.1016/j.ajpath.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Urinary miR-126, miR-155, and miR-29b with Diabetic Kidney Disease

Abstract: Effective diabetic kidney disease (DKD) biomarkers remain elusive, and urinary miRNAs represent a potential source of novel noninvasive disease sentinels. We profiled 754 miRNAs in pooled urine samples from DKD patients (n = 20), detecting significantly increased miR-126, miR-155, and miR-29b compared with controls (n = 20). These results were confirmed in an independent cohort of 89 DKD patients, 62 diabetic patients without DKD, and 41 controls: miR-126 (2.8-fold increase; P < 0.0001), miR-155 (1.8-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 47 publications
3
76
0
1
Order By: Relevance
“…5 An interesting approach for therapeutic intervention in diabetes would be cell-specific delivery of these molecules. Urine is an attractive source of molecular markers for DN [6][7][8][9][10][11][12][13] (Table 1). Urine miRNA levels might be reflective of the intrinsic kidney tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…5 An interesting approach for therapeutic intervention in diabetes would be cell-specific delivery of these molecules. Urine is an attractive source of molecular markers for DN [6][7][8][9][10][11][12][13] (Table 1). Urine miRNA levels might be reflective of the intrinsic kidney tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…miR‐126 regulates gene transcription, translation, and degradation of mRNAs, which has been researched regarding its role in the pathogenesis of inflammation, autoimmunity, and organ failures. For instance, high miR‐126 level is associated with the development of kidney injury in diabetic patients and chronic kidney disease patients 6,7 . Furthermore, miR‐126 participates in the pathogenesis of active ulcerative colitis via regulating NF‐kappa B inhibitor (Iκ‐Bα) 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) regulate the expression of target genes [ 15 ]. Previous studies showed that the expression level of miR-155 was downregulated in tissues and urine samples of DN patients [ 16 , 17 ]. The abnormal expression of miR-155-5p in DN patients may be related to the disease stage of patients or the pathogenesis of DN [ 17 ].…”
Section: Introductionmentioning
confidence: 99%